2014
DOI: 10.1177/0194599814528659
|View full text |Cite
|
Sign up to set email alerts
|

Lean Six Sigma Applied to Ultrasound Guided Needle Biopsy in the Head and Neck

Abstract: Lean Six Sigma reduces waste and optimizes quality and accuracy in manufacturing. This is the first known application of Lean Six Sigma to office-based USFNA in the evaluation of head and neck lesions. The literature supports the value of office-based ultrasound to patients and health care systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…18,19 Increasing the efficiency of hospital-based clinical care by applying LH was identified as a potent strategy for lowering costs and improving outcomes. 20 Some areas where LH has been implemented include: intensive care units (ICUs), 21 cardiology, 22 surgery, 23 gynecologic oncology, 24 colonoscopy, 25 pathology, 26 radiology, 27 mental health units, 28 eye hospitals, 29 otolaryngology, 30 ultrasound-otolaryngology, 31 organ transplant centers, 32 and clinical laboratories, 33 to name but a few. In the United States, a national survey found that around 70% of hospitals use LH or related approaches.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Increasing the efficiency of hospital-based clinical care by applying LH was identified as a potent strategy for lowering costs and improving outcomes. 20 Some areas where LH has been implemented include: intensive care units (ICUs), 21 cardiology, 22 surgery, 23 gynecologic oncology, 24 colonoscopy, 25 pathology, 26 radiology, 27 mental health units, 28 eye hospitals, 29 otolaryngology, 30 ultrasound-otolaryngology, 31 organ transplant centers, 32 and clinical laboratories, 33 to name but a few. In the United States, a national survey found that around 70% of hospitals use LH or related approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Our literature search in PubMed identified 31 articles studying the application of Lean management to improve patient flow in an outpatient clinic setting. Matt et al 13 previously reported the value of Lean strategies to reduce cost, time to diagnosis, and improve office‐based FNA workflow process. However, to our knowledge, this is the first study to apply Lean principles along with unsophisticated, open‐source technology such as Google Drive, iOS apps, and barcodes to develop a customized, cost‐effective inventory management system for maximizing FNA clinic workflow.…”
Section: Discussionmentioning
confidence: 99%
“…Matt et al demonstrated that office‐based biopsies of head and neck masses decreased time to diagnosis, patient travel, and unnecessary laboratory and imaging studies. This enhanced patient convenience and staff satisfaction while reducing costs and risks associated with diagnosis . Collar et al instituted automated paging and enhanced paperwork availability to streamline perioperative processes, effectively reducing unutilized operating room (OR) time .…”
Section: Introductionmentioning
confidence: 99%